Metal Analysis Reformulation of Subcutaneous Injectables into Alternative Delivery Methods: A Meta-Analysis: patient adherence - malkawi, ruba (Jadara Journal of Social Sciences, 2025)
This meta-analysis evaluates the reformulation of drugs initially intended for subcutaneous (SC) injection into alternative delivery methods, such as oral, transdermal, and nasal administration. A thorough examination of research comparing the effectiveness, safety, patient compliance, and pharmacokinetics (PK) of modified and traditional subcutaneous formulations, this study provides a complete evaluation of the medical results connected with alternative delivery methods to injections. Results show that different ways of administering treatment can offer similar effectiveness with better patient compliance, mainly because of increased convenience and decreased invasiveness. The study also emphasizes the difficulties in maintaining drug absorption through oral and nasal administration, showing the potential and intricacy of reaching the same therapeutic effect. This research provides important knowledge for healthcare providers, drug researchers, and others involved in healthcare, supporting the development of patient-focused medication delivery advancements that improve both medical results and adherence.